Efficacy of In-Service Education and Training (INSET) Courses in Improving EFL Teachers’ Technological Pedagogical and Content Knowledge (TPACK) - Maryam Mahmoudi; Mojgan Rashtchi; Gholam-Reza Abbasian (Journal of Modern Research in English Language Studies)
Teachers’ knowledge base refers to what teachers should know and be able to implement in their classes. This study investigated to what extent in-service education and training (INSET) courses were influential in developing teachers’ knowledge base. From different models, the researchers selected Mishra and Koehler’s (2006) technological pedagogical and content knowledge (TPACK) model that assumes an interrelationship between the components of teachers’ knowledge base. Thus, an exploratory sequential mixed methods study was designed in three phases. In the first phase, the questionnaire of English Language Teacher’s Knowledge Base (ELTKB) was developed and validated with 335 randomly selected EFL teachers from Guilan province. In the second phase, the quantitative follow-up phase, twenty-nine 11th grade EFL teachers’ knowledge base improvement was examined after attending online INSET classes. The results of the paired sample t-tests revealed statistically significant differences between the participants’ knowledge base components before and after the courses. In the third phase, semi-structured interviews explored the participants’ viewpoints concerning the content of the INSET courses. The teachers’ perceptions declared in interview sessions were not in complete conformity with the results obtained from the second phase of the study. The teachers had some complaints about the content of the courses and provided some suggestions. The findings of this study can benefit teacher educators, policymakers, INSET programmers, and English teachers. Also, the ELTKB can be employed by researchers as a valid tool for measuring TPACK that is an essential concept for explaining the relationship between teachers’ content, pedagogy, and technology-related knowledge.